2021
DOI: 10.26525/jtfs2021.33.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Visitors’ Willingness to Pay for Entrance Fee at Puncak Janing Forest Eco-Park, Kedah, Malaysia

Abstract: The aim of this study was to determine visitors' willingness to pay for conservation fee at Puncak Janing Forest Eco-Park in Kedah, Malaysia. Three hundred visitors of the park were selected using convenience sampling. The findings showed that that willingness to pay for each household using double bounded contingent valuation method was RM18.53 per annum. The findings can be used for policy implementation and improve forest conservation projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
1
1
Order By: Relevance
“…Only the age and income factors of the three variables tested were statistically significant. This value was lower than those in previous studies by Farah Hanim et al (2021), Muhammad Fairus andNurin Fadhlin et al (2021), which utilised Stata to analyse the data for doublebound CVM, in which the Wald chi-squared values were 12.64, 17.22 and 27.86, respectively. However, it should be emphasised that the number of variables found to be significant was more than two, but only two variables were found to be significant in this study.…”
Section: Logit Regression Analysiscontrasting
confidence: 63%
“…Only the age and income factors of the three variables tested were statistically significant. This value was lower than those in previous studies by Farah Hanim et al (2021), Muhammad Fairus andNurin Fadhlin et al (2021), which utilised Stata to analyse the data for doublebound CVM, in which the Wald chi-squared values were 12.64, 17.22 and 27.86, respectively. However, it should be emphasised that the number of variables found to be significant was more than two, but only two variables were found to be significant in this study.…”
Section: Logit Regression Analysiscontrasting
confidence: 63%
“…The single-bounded dichotomous evaluation method has been employed to examine the economic value of ecosystem services in empirical studies [52][53][54][55] due to the simplicity and efficiency of the interview and analysis processes, despite considerable discussion of potential problems since its early use by Bishop, Heberlein, and Kealy [56]. Moreover, the evaluation has significance in the empirical application in ecology assessment [57][58][59][60].…”
Section: Contingent Valuation Methodsmentioning
confidence: 99%
“…In general, the higher an individual's level of education, the more likely they are to be WTP (Fadhlin et al 2021). Witt (2019) and Zaiton et al (2019) found a positive correlation between education levels.…”
Section: Estimated Wtp For Biodiversity Conservation Among Visitorsmentioning
confidence: 95%
“…Ghous and Siddiqui (2022) and Truong (2022) discovered identical results when most respondents agreed to pay due to their awareness of preserving and conserving biodiversity. Moreover, according to a study by Fadhlin et al (2021), respondents' attitudes significantly affected their WTP for conservation fees. The WTP is significantly influenced by the level of awareness regarding biodiversity conservation, as human attitudes and preferences shape it, indicating their sensitivity toward the issues arising from the possible extinction of these biodiversity resources (Musa and Nadarajah 2023).…”
Section: Willingness To Pay For Biodiversity Conservationmentioning
confidence: 99%